Contamination of organic nutrient sources with potentially toxic elements, antibiotics and pathogen microorganisms in relation to P fertilizer potential and treatment options for the production of sustainable fertilizers : A review - Bloem, E.; Albihn, A.; Elving, J.; Hermann, L.; Lehmann, L.; Sarvi, Minna; Schaar, T.; Schick, J.; Turtola, Eila; Ylivainio, Kari (Elsevier, 2017)
Organic nutrient sources such as farmyard manure, sewage sludge, their biogas digestates or other animal by-products can be valuable fertilizers delivering organic matter to the soil. Currently, especially phosphorus (P) is in the focus of research since it is an essential plant nutrient with finite resources, estimated to last only for some more decades. Efficient utilization of organic P sources in agriculture will help to preserve P resources and thereby has the potential to close nutrient cycles and prevent unwanted P-losses to the environment, one of the major causes for eutrophication of water bodies. Unfortunately, organic P sources usually contain also various detrimental substances, such as potentially toxic elements or organic contaminants like pharmaceuticals as well as pathogenic microorganisms. Additionally, the utilization of some of these substrates such as sewage sludge or animal by-products is legally limited in agriculture because of the potential risk to contaminate sites with potentially toxic elements and organic contaminants. Thus, to close nutrient cycles it is important to develop solutions for the responsible use of organic nutrient sources. The aim of this review is to give an overview of the contamination of the most important organic nutrient sources with potentially toxic elements, antibiotics (as one important organic contaminant) and pathogenic microorganisms. Changes in manure and sewage sludge management as well as the increasing trend to use such substrates in biogas plants will be discussed with respect to potential risks posed to soils and water bodies. Some examples for abatement options by which contamination can be reduced to produce P fertilizers with high amounts of plant available P forms are presented.
Keywords: thermo chemical treatment; antibiotics; trace elements; pathogens; phosphorus; recycling